Structural equations of the relationship between the psychological needs of male and female employees with the experience of being overwhelmed at work with the mediation of organizational commitment - Attaran, Elnaz; Tizdast, Taher; Zarbakhsh Bahri, Mohammad Reza (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: The current research was conducted with the aim of structural equations of the relationship between the psychological needs of employees and the experience of being overwhelmed at work with the mediation of organizational commitment. Methods: The method of the current research was of the correlation type and the method of structural equations was used. All the employees of the Islamic Azad Universities of Tehran in the academic year of 2020-21 formed the statistical population of the present study, and 339 employees were selected as a sample using random sampling. To collect data, a questionnaire tool was used: a questionnaire on the experience of drowning in work (Talabeigi, 2013), psychological needs (Deci & Ryan, 2000) and an organizational commitment questionnaire (Allen & Mayer, 1997) were the research tools, which were reliable and valid. Questionnaires in this research were calculated using Cronbach's alpha 0.865, 0.921 and 0.793 respectively for the aforementioned questionnaires. To analyze the data, Pearson correlation coefficient and structural equation model were used and using software SPSS 24 and AMOS 24 were used. Results: The results of the analysis showed that there is a significant positive and direct relationship between the psychological needs of employees with the experience of drowning in work and the organizational commitment of the organization (P ≥ 0.05). Also, the results of structural equation analysis showed that organizational commitment mediates the relationship between employees' psychological needs and the experience of being overwhelmed at work (P ≥ 0.05).Conclusion: Attention and emphasis on promoting organizational commitment help creating a clear image of effective human resources with appropriate psychological needs and the experience of drowning in work.